Taxation of carbon emissions and air pollution in intertemporal optimization frameworks with social and private discount rates - Mathias Mier; Jacqueline Adelowo; Christoph Weissbart (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
Current policies focus on reducing CO2 emissions, neglecting the existence and impact of other air pollutants such as NO2, NH3, NMVOC, PPM10, PPM2.5, and SO2. We devise a strategy to model those emissions and related social cost accounting for diverging social and private discount rates in an intertemporal optimization framework that aims to predict firm behavior. We derive optimal CO2 and air pollution taxes above the social cost of carbon or social cost of air pollution, respectively, when social discount rates are below private ones. We implement the modeling strategy in the EUREGEN model to determine the technology and emission mix of the European power market until 2050 and quantify aggregated social cost. No taxation yields aggregated social cost of 5,145 billion exteuro in the period 2020 to 2050. Taxing CO2 emissions only leads to aggregated social cost of 794 billion exteuro and promotes the deployment of CCS technologies. Taxing air pollution only results in aggregated social cost of 2,091 billion exteuro and fosters the deployment of nuclear. Taxing both reduces cost to 622 billion exteuro. Wind and solar are almost unaffected by internalization choices.
Keywords: C61; C68; Q40; Q41; 330; Taxation; intertemporal optimization; social cost; air pollution; carbon emission; externality; energy system model; power market model; decarbonization